Virtual Reality: A Potential Technology for Providing Novel Perspective to Novice Driver Education in Malaysia. - Chen, Chwen Jen; Toh, S.C.; Wan, M.F. (2003)
Three-dimensional virtual reality offers a number of unique attributes that are unavailable in any other existing educational media. Indeed, this technology, if placed in a sound educational framework, would provide a powerful and stimulating learning environment. We discuss some observations of the current methods of instruction for educating novice drivers in Malaysia, particularly from the cognitive aspect. It then highlights the potential of applying virtual reality technology to overcome the observed problems and the feasibility of its implementation.